Thyroid Disrupting Effects of Old and New Generation PFAS - Coperchini, Francesca; Croce, Laura; Ricci, Gianluca; Magri, Flavia; Rotondi, Mario; Imbriani, Marcello; Chiovato, Luca (Frontiers in Endocrinology, 2021)
Per- and polyfluoroalkyl substances (PFAS) represent a group of synthetic compounds widely used in industry plants since many years due to their surfactant properties, thermic and flam resistance and their low grade of degradation. These characteristics, useful for the industrial production, are however potentially dangerous for human health and for the environment. PFAS are persistent pollutants accumulating in waters and soil and recoverable in foods due to their release by food packaging. Humans are daily exposed to PFAS because these compounds are ubiquitous and, when assimilated, they are difficult to be eliminated persisting for years both in humans and animals. Due to their persistence and potential danger to health, some old generation PFAS have been replaced by newly synthesized PFAS with the aim to use alternative compounds presumably safer for humans and the environment. Yet, the environmental pollution with PFAS remains a matter of concern worldwide and led to large-scale epidemiological studies both on plants’ workers and on exposed people in the general population. In this context, strong concern emerged concerning the potential adverse effects of PFAS on the thyroid gland. Thyroid hormones play a critical role in the regulation of metabolism, and thyroid function is related to cardiovascular disease, fertility, and fetal neurodevelopment. In vitro, ex vivo data and epidemiological studies suggested that PFASs may disrupt the thyroid hormone system in humans, with possible negative repercussions on the outcome of pregnancy and fetal-child development. However, data on the thyroid disrupting effect of PFAS remain controversial, as well as their impact on human health in different ages of life. Aim of the present paper is to review recent data on the effects of old and new generation PFAS on thyroid homeostasis. To this purpose we collected information from in vitro studies, animal models and in vivo data on exposed workers, general population and pregnant women.